Folic acid-modified ROS-responsive nanoparticles encapsulating luteolin for targeted breast cancer treatment. (1st January 2021) - Wang, Yu; Wang, Qianmei; Feng, Wei; Yuan, Qian; Qi, Xiaowei; Chen, Sheng; Yao, Pu; Dai, Qing; Xia, Peiyuan; Zhang, Dinglin; Sun, Fengjun
Abstract: Luteolin (Lut) is a natural flavonoid polyphenolic compound with multiple pharmacological activities, such as anti-oxidant, anti-inflammatory, and anti-tumor effects. However, the poor aqueous solubility and low bioactivity of Lut restrict its clinical translation. Herein, we developed a reactive oxygen species (ROS)-responsive nanoplatforms to improve the bioactivity of Lut. Folic acid (FA) was employed to decorate the nanoparticles (NPs) to enhance its targeting ability. The size of Lut-loaded ROS-responsive nanoparticles (Lut/Oxi-αCD NPs) and FA-modified Lut/Oxi-αCD NPs (Lut/FA-Oxi-αCD NPs) is 210.5 ± 6.1 and 196.7 ± 1.8 nm, respectively. Both Lut/Oxi-αCD NPs and Lut/FA-Oxi-αCD NPs have high drug loading (14.83 ± 3.50 and 16.37 ± 1.47%, respectively). In vitro cellular assays verified that these NPs could be efficiently internalized by 4T1 cells and the released Lut from NPs could inhibit tumor cells proliferation significantly. Animal experiments demonstrated that Lut/Oxi-αCD NPs, especially Lut/FA-Oxi-αCD NPs obviously accumulated at tumor sites, and inhibited tumor growth ∼3 times compared to the Lut group. In conclusion, the antitumor efficacy of Lut was dramatically improved by targeting delivery with the ROS-responsive nanoplatforms.